CENPF as a prognostic marker of glioma: unraveling the molecular mechanisms - Xiuyang Chen; Yiwei Wu; Yining Xing; Peng Zhong (Journal of Cancer Research and Clinical Oncology)
Abstract Objective Glioma is the dominant primary intracranial malignancy. The roles of CENPF and the CENPF - p53 axis in glioma remain elusive. This study uses bioinformatics and animal experiments to clarify the relationship between CENPF and p53 in glioma. CENPF affects spindle assembly and chromosomal segregation, while p53 is a tumor—suppressor gene. Their dysregulation may interact and impact glioma development. Our research aims to uncover the underlying molecular mechanisms, offering new perspectives for glioma diagnosis and treatment. Method Gene expression data from the Gene Expression Omnibus (GEO) database ( http://www.ncbi.nlm.nih.gov/geo/ ) were retrieved, specifically datasets GSE50161, GSE104291, and GSE12249. Volcano plots were generated to visualize differentially expressed genes (DEGs), and intersecting DEGs were identified using Venn diagrams. Weighted gene co-expression network analysis (WGCNA) was employed to construct and analyze the protein–protein interaction (PPI) network. Additionally, gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were conducted. Gene set enrichment analysis (GSEA) was utilized for comprehensive GO and KEGG analyses of the entire genome. Comparative Toxicogenomics Database (CTD) analysis was performed, and TargetScan was used to identify miRNAs regulating central DEGs. An animal model of glioma was established and analyzed via Western blot. Result A total of 501 differentially expressed genes (DEGs) were identified, from which eight significant modules were generated and ten core genes were extracted. These core genes exhibited differential expression patterns between glioma tumor and non-tumor samples. Expression analysis revealed that the ten core genes associated with glioma (CENPF, PBK, ASPM, KIF2C, KIF20A, CDC20, TOP2A, NUSAP1, TTK, KIF23) were significantly upregulated in tumor tissues (P < 0.05). They are primarily enriched in protein signal transduction, coated membrane structures, AP-type membrane coat adaptor complexes, and chloride channel activity. KEGG pathway analysis indicated that these target genes were mainly involved in nicotine addiction, arginine and proline metabolism, beta-alanine metabolism, and histidine metabolism. The mouse model confirmed that CENPF and CDK-1 were highly expressed in glioma tissues, while p53, p21, and Caspase9 were downregulated, leading to inhibition of the apoptosis pathway and exacerbation of glioma progression. Overexpression of CENPF further suppressed key molecules in the p53-mediated apoptosis pathway. Conversely, low expression of CENPF activated these key molecules, inducing apoptosis in glioma cells. Conclusions CENPF exhibits elevated expression levels in glioma, potentially inhibiting cell apoptosis via the p53 signaling pathway, consequently contributing to the onset and progression of glioma.